Riset Hadis Multimedia - Ali Mukta Siregar; Rahmi Syahriza; Tonang Lubis (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study examines the development and implementation of multimedia-based hadith research in the context of contemporary Islamic studies. The advancement of digital technology has transformed traditional hadith studies, which were previously text-centered, into a more integrative approach involving audio, visual, and interactive media. This research aims to analyze how multimedia tools contribute to the preservation, interpretation, and dissemination of hadith knowledge while maintaining methodological rigor in sanad and matn analysis. Using a qualitative descriptive method through literature review and content analysis, this study explores various multimedia platforms such as digital hadith databases, visual narration, and interactive learning media. The findings indicate that multimedia-based hadith research enhances accessibility, learning engagement, and public understanding, especially among younger generations, without diminishing the authenticity principles of hadith scholarship. Therefore, multimedia integration represents a strategic innovation for strengthening Islamic knowledge transmission in the digital era. Keywords: hadith studies, multimedia research, digital islamic studies, religious communication Abstrak Penelitian ini mengkaji perkembangan dan penerapan riset hadis berbasis multimedia dalam konteks studi Islam kontemporer. Kemajuan teknologi digital telah menggeser kajian hadis yang sebelumnya berfokus pada teks menjadi pendekatan yang lebih integratif melalui pemanfaatan media audio, visual, dan interaktif. Penelitian ini bertujuan untuk menganalisis kontribusi multimedia dalam pelestarian, pemahaman, dan penyebaran ilmu hadis tanpa mengabaikan ketelitian metodologis dalam kajian sanad dan matan. Metode yang digunakan adalah deskriptif kualitatif melalui studi pustaka dan analisis konten terhadap berbagai platform multimedia, seperti basis data hadis digital, visualisasi narasi hadis, dan media pembelajaran interaktif. Hasil penelitian menunjukkan bahwa riset hadis berbasis multimedia mampu meningkatkan aksesibilitas, keterlibatan pembelajaran, serta pemahaman masyarakat, khususnya generasi muda, dengan tetap menjaga prinsip autentisitas keilmuan hadis. Dengan demikian, integrasi multimedia menjadi inovasi strategis dalam penguatan transmisi pengetahuan Islam di era digital. Kata Kunci: kajian hadis, riset multimedia, studi Islam digital, komunikasi keagamaan